Kesehatan Jasmani dan Rohani Menurut Al-Qur’an dan Hadist - Nur, Nur Shofiatul (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2023)
It is undeniable that in human life health is one of the primary aspects that cannot be ignored. Then it will be described in this scientific work how aspects of health with the Al-Qur'an and Hadith. Where the Al-Qur'an and Hadith are the guidelines for Muslims. The description in this paper will begin with a brief review of the Qur'an, Hadith and health. Then it will be explained more clearly to maintain physical and spiritual health that goes hand in hand with worship to Allah SAW. Sincere intentions because Allah will make everything we do in an effort to protect ourselves from disease will be worth worship. Among the Islamic ways of maintaining health by maintaining cleanliness and carrying out ritual ablution and bathing regularly for every Muslim. Healthy is a physical condition in which all functions are in a healthy state. Being cured after an illness is the best gift from Allah to humans. Obligatory prayers at the beginning of time, reading more of the Koran and stories of the prophets and messengers.